Cores, cheiros, sons, saberes e fazeres : feira de Lagarto/SE - Santos, Vanessa Modesto dos (2018)
The fairs are representations of the oldest forms of commercialization of products, conforming a place with particularities and spatialities, replete of colors, sounds, smells, movements and sociocultural links. The geography of the fairs in the Northeast region is permeated by peculiarities, being possible to find in its territory products of diverse origins. Their periocity is associated with their organization from each place it usually happens on alternate days in the surrounding space. The residents of more distant communities move to commercialize the fruit of their production as well as buy products they need for they survival. In this work we took as spacial indention the city of Lagarto/SE which is located in the south-central region of the state, in order to understand the social, cultural and economic dynamics of the fairs held at Lagarto/SE. In this city we observed that the fair happens on Sundays, Mondays, Thursdays and Saturdays and it is rooted in population identity who demand agricultural products, traditional food, meat, clothing, footwear, live animals and industrialized products, in addition to assets of miscellaneous consumption. The used methodology is of qualitative feature and it is based on review of literature and research in loco - which we perform semi-structured interview with marketers and consumers, using the field diary as an auxiliar tool for the researcher to perform later the analysis to obtain information for the organization of the dissertation. The configuration of the market space of the fair is inserted in the market of the informal sector, and its relations are based, mainly, on the use of the liquid money, indispensable for the social and economic reproduction of the inserted family groups. In addition to commercial space, the fairs are a place of encounter, exchange, a territory marked by a mixture of colors, sounds, smells, tastes, signs and meanings, and the diversity of actions, functions and activities. It is common to see in the network of actors in question the relations of power, especially from the municipal inspectors and guards who exert it in the sense of delimiting the microterritories of the marketers, and sometimes they get involved in conflicts solved in the place. However, in contrast to this characteristic, we have demonstrated the constitution and strengthening of relations of sociability and proximity between the groups of marketers, as well as between marketers and consumers, relations permeated by trust, so that in the act of " make the fair ", bonds of friendship are becoming established. The day of the fair is not only an eminently economic meeting, but a differentiated day in which experiences, knowledge and actions are shared and social networks are strengthened.